2007
DOI: 10.1073/pnas.0606702104
|View full text |Cite
|
Sign up to set email alerts
|

SUMO modification regulates inactivation of the voltage-gated potassium channel Kv1.5

Abstract: The voltage-gated potassium (Kv) channel Kv1.5 mediates the IKur repolarizing current in human atrial myocytes and regulates vascular tone in multiple peripheral vascular beds. Understanding the complex regulation of Kv1.5 function is of substantial interest because it represents a promising pharmacological target for the treatment of atrial fibrillation and hypoxic pulmonary hypertension. Herein we demonstrate that posttranslational modification of Kv1.5 by small ubiquitin-like modifier (SUMO) proteins modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 51 publications
(71 reference statements)
4
116
1
Order By: Relevance
“…3). It is important to note that although this suggests preferential conjugation, we have observed a similar pattern for other SUMOylation targets (37), and the detection of modified species is likely to reflect in large part the differential expression of the SUMO isoforms rather than an intrinsic property of FOXC1/C2. To determine the role of the motifs identified by sequence comparison in SUMO modification, we replaced the predicted target Lys residues with Arg, which does not support SUMOylation.…”
Section: Foxc1 and Foxc2 Harbor Conserved Sc/sumoylationmentioning
confidence: 93%
“…3). It is important to note that although this suggests preferential conjugation, we have observed a similar pattern for other SUMOylation targets (37), and the detection of modified species is likely to reflect in large part the differential expression of the SUMO isoforms rather than an intrinsic property of FOXC1/C2. To determine the role of the motifs identified by sequence comparison in SUMO modification, we replaced the predicted target Lys residues with Arg, which does not support SUMOylation.…”
Section: Foxc1 and Foxc2 Harbor Conserved Sc/sumoylationmentioning
confidence: 93%
“…Furthermore, several SUMO target proteins have important acute effects on neuronal functions. 26 Such proteins include the mRNA-binding protein La, 27 the kainate receptor subunit GluR6 28 and the potassium channel Kv1.5, 29 suggesting a role for SUMO conjugation in ion fluxes and neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…In response to oxidative stress, a sulfenic acid modification has been reported on a cysteine residue present in the C-terminal domain of K V 1.5 that triggers internalisation of K V 1.5, decreases current density, and diverts the channel from the recycling endosome towards degradation [75]. Moreover, tyrosine phosphorylation of K V 1.5 and redox-sensitive K V 1.5 sumoylation were also reported leading to its inactivation [35,73]. Using Xenopus oocytes as a model to study ion channels in a controlled in vivo environment, it was demonstrated that expression of the ubiquitin ligase Nedd4-2 declined K V 1.5 currents by ubiquitinating and thereby reducing K V 1.5 plasma membrane expression [74].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%
“…Protein post-translational modification (PTM) is a highly dynamic and crucial mechanism in which the functional properties of a protein are altered by the covalent addition of a chemical group or protein to its amino-acid residues. Independently of PAH, K V 1.5 has been shown to undergo diverse, reversible or irreversible PTM, including phosphorylation, S-acylation, palmitoylation, sumoylation, ubiquitination and glycosylation, which impact on ion channel expression, channel trafficking to the membrane, stability and activity [35,[70][71][72][73][74]. In response to oxidative stress, a sulfenic acid modification has been reported on a cysteine residue present in the C-terminal domain of K V 1.5 that triggers internalisation of K V 1.5, decreases current density, and diverts the channel from the recycling endosome towards degradation [75].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%